Isoliensinine Induces Ferroptosis in Urothelial Carcinoma Cells via the PI3K/AKT/HIF-1α Axis: Molecular Evidence from Next-Generation Sequencing - Yun-Chen Li; Hsuan-En Huang; Chia-Ying Yu; Ya-Chuan Chang; Shu-Yu Lin; Shao-Chuan Wang; Wen-Wei Sung (Pharmaceuticals, 2025)
Background: Bladder cancer ranks ninth among the most commonly diagnosed cancers, with urothelial carcinoma (UC) accounting for more than 90% of all cases. Given the high recurrence rate and progression risk of bladder cancer, investigating alternative adjunct therapies is imperative. One potential candidate is isoliensinine, which has shown antitumor potential in various cancers; however, the effectiveness of isoliensinine on UC is largely unknown. Methods: In the present study, the effects of isoliensinine on UC cells were examined in a variety of in vitro experiments, including MTT assays, colony formation assays, flow cytometry assays, RNA sequencing analysis, and Western blotting. Results: The isoliensinine-treated T24 and UMUC3 UC cell lines showed cell growth inhibition and proliferation in the MTT and colony formation assays and an apoptotic effect in the flow cytometry assays. RNA sequencing analysis, performed to explain the underlying mechanisms, revealed a significant regulation of cell functions, including apoptosis, the cell cycle, hypoxia-inducible factor 1 (HIF-1) signaling, tumor necrosis factor (TNF) signaling, and ferroptosis. Subsequent Western blotting results verified all these findings. Conclusions: Overall, our data indicate that isoliensinine inhibits UC cell growth and proliferation by inducing apoptosis through alterations in the TNF and HIF1 pathways and ferroptosis. Overall, isoliensinine shows potential for use in new or combined adjunct therapies for the treatment of bladder cancer.